Chronic cancer pain management by the nursing team - Anara da Luz Oliveira; Natália da Palma Sobrinho; Beatriz Aparecida Silva Cunha (Revista Dor)
ABSTRACT BACKGROUND AND OBJECTIVES: Cancer patients' pain is related to the tumor, to diagnostic and therapeutic procedures and to the terminality of the disease; however health professionals, especially nursing teams, still have difficulties in evaluating and managing pain. As from experience in hospitals, it was noticed that nursing teams face barriers, which is intensified in case of cancer patients, marked by the "incurable" cancer pain stigma. This study aimed at identifying in the literature, how nursing teams manage chronic cancer pain. CONTENTS: We have found 710 articles being 194 in LI-LACS and 516 in Scielo, being included 14 articles by means of the descriptors "Nursing Care", "Nursing", Chronic pain", "Pain management", "Oncology". In the category "Cancer pain management by the nursing team", studies have reinforced the importance of pain evaluation by the nursing team and present resources and strategies to make it effective. In the category "Pharmacological methods for pain management", drugs appear as the first method of choice with the three steps stair of the World Health Organization and opiophobia is discussed. In the category "Non-pharmacological methods for pain management", there are interventions such as therapeutic massage, spiritual support and comfort measures, such as changing position. CONCLUSION: Assisting painful cancer patients goes beyond performing procedures; it is necessary to think about scientific knowledge acquisition and professional-patient link for a safe assistance when managing cancer pain.